Compression of Three-Dimensional Terrain Data Using Lifting Scheme Based on Second Generation Wavelets - Pradhan, Biswajeet (2006)
The most complex GIS data are three dimensional terrain data. In GIS applications, for a realistic representation of a terrain the Digital Elevation Model (DEM) is not suitable for direct use in online GIS services due to its large size and inflexibility data structure. Triangulated Irregular Network (TIN), another popular data format for three dimensional data, requires great number of triangles. These triangles that represent the surface of the terrain ultimately increase the data size. For online GIS interactive programs it has become highly essential to reduce the number of triangles in order to save storage space. Existing image compression systems for GIS terrain data have bandwidth and image size constraints that result in time-consuming transmission of uncompressed raw terrain data. Thus image compression is a key factor to improve transmission speed and storage, but it risks losing relevant terrain information. Moreover, most of these algorithms are based either on Fourier transmission or on first order wavelet techniques. Very little work has been done till date on the GIS terrain data compression based on second generation wavelets. Second generation wavelet technology provides an efficient compression tool to achieve high compression ratio while maintaining an acceptable fidelity of surface quality.